PARAMETRIC STUDY ON THE BEHAVIOUR OF POST-TENSIONED RECTANGULAR AND TRAPEZOIDAL BOX-GIRDER BRIDGES USING FEM AND CLASSICAL METHODS - Nandana P; Mamatha K J (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Box-girder bridges, characterized by their hollow box-shaped sections, are widely used in modern infrastructure due to their high torsional rigidity, flexural strength, and aesthetic appeal. This study investigates the structural performance of two common box-girder cross-sections—rectangular and trapezoidal—under various loading conditions. A simply supported, single-cell post-tensioned concrete box-girder of 40 m span is analyzed. Dimensions are determined as per IRC-18 and subjected to Class A and Class 70R vehicular loading as per IRC-6. Both classical beam theory and finite element method (FEM) using CSI Bridge software are employed. Results show that the rectangular section demonstrates higher torsional shear stress (by 45%) but lower deflection compared to the trapezoidal section. The bending stress in the rectangular section is 13% lower than in the trapezoidal section. Additionally, prestress loss is found to be 5% higher in the rectangular section. The FEM results closely match manual calculations, validating the modeling approach. This study provides comparative insights into the performance of typical box-girder geometries, aiding in more effective design selection for medium-span bridges.